2022
DOI: 10.2147/dmso.s375300
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of the Correlation Between the Atherogenic Index of Plasma and Nonalcoholic Fatty Liver Disease in Patients with Type 2 Diabetes

Abstract: Purpose The main objective of this study was to examine the possible association between the atherogenic index of plasma (AIP) and the prevalence of nonalcoholic fatty liver disease (NAFLD) in Chinese individuals with type 2 diabetes mellitus (T2DM). Patients and methods In this survey, data from 1074 patients with T2DM were retrospectively extracted. The correlations between each variable and NAFLD were determined by univariate analysis, and then, the statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…AIP exhibited superior discriminatory capability compared to other lipid markers in the prediction of hyperuricemia. Lin et al [ 40 ] demonstrated that AIP served as a robust independent risk factor for NAFLD among patients with type 2 diabetes. In addition, they assessed the diagnostic ability of AIP for NAFLD using a subject operating characteristic curve with a specificity and sensitivity of 90.1% and 65%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…AIP exhibited superior discriminatory capability compared to other lipid markers in the prediction of hyperuricemia. Lin et al [ 40 ] demonstrated that AIP served as a robust independent risk factor for NAFLD among patients with type 2 diabetes. In addition, they assessed the diagnostic ability of AIP for NAFLD using a subject operating characteristic curve with a specificity and sensitivity of 90.1% and 65%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The National Health and Nutrition Examination Survey (NHANES) is one of the main programs of the National Center for Health Statistics (NCHS) and this program aims to assess the health and nutritional status of adults and children in the United States 21 . Since 1999, health data gathered by interviews, physical exams, and laboratory testing from representative American population samples would be published in their official website every two years 22 , and also ongoing follow-up mortality data would be posted in the National Death Index death certificate records (www.cdc.gov/nchs/data-linkage/mortalitypublic.htm).…”
Section: Methods Data Source and Study Populationmentioning
confidence: 99%
“…Studies have also discovered a strong association between AIP and T2DM [ 11 , 12 ], with higher AIP levels indicating an increased risk of developing T2DM. Research on the correlation between AIP and T2DM has extensively examined individuals with different glycemic statuses, such as those with coronary heart disease [ 13 ], nonalcoholic fatty liver disease [ 14 ], prediabetes [ 5 ], and American adults diagnosed with T2DM in the National Health and Nutrition Examination Survey (NHANES) database [ 11 ]. Although obesity is a principal cause of insulin resistance among diabetic patients and an independent risk factor for T2DM and its complications, as well as all-cause mortality [ 15 , 16 ], the association between the AIP and T2DM, particularly in individuals who are overweight and obese, has not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%